2017
DOI: 10.1038/s41598-017-14954-0
|View full text |Cite
|
Sign up to set email alerts
|

Neural basis of forward flight control and landing in honeybees

Abstract: The impressive repertoire of honeybee visually guided behaviors, and their ability to learn has made them an important tool for elucidating the visual basis of behavior. Like other insects, bees perform optomotor course correction to optic flow, a response that is dependent on the spatial structure of the visual environment. However, bees can also distinguish the speed of image motion during forward flight and landing, as well as estimate flight distances (odometry), irrespective of the visual scene. The neura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…And the responses weakly depend on the spatial period of the grating. This coincides with the responses of the descending neurons according to Ibbotson's records [10,14]. And this is important for insects estimating flight speed or gauging distance of foraging journey in a clutter environment.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…And the responses weakly depend on the spatial period of the grating. This coincides with the responses of the descending neurons according to Ibbotson's records [10,14]. And this is important for insects estimating flight speed or gauging distance of foraging journey in a clutter environment.…”
Section: Resultssupporting
confidence: 75%
“…We simulated the OFF pathway of the Drosophila's visual neural circuits when the sinusoidal grating moving in preferred direction. The normalized responses of AVDM over different velocities and spatial periods in contrast of experimental results [14] can been seen from Fig. 4.…”
Section: Resultsmentioning
confidence: 93%
“…The relatively dorsal site of our lobular injection site is compatible with the location of the layer 1–4 dendrites which are involved in motion detection in bumblebees (Paulk, Phillips‐Portillo, Dacks, Fellous, & Gronenberg, ). The tract also resembles the POT1 (posterior optic tract 1) which lies in close proximity to presynaptic endings of descending “optomotor neurons” that are able to detect rotational image flow (Ibbotson, Hung, Meffin, Boeddeker, & Srinivasan, ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in bees revealed descending neurons in the ventral nerve cord monotonically increased their median firing rate with the angular velocity of a frontally presented rotating spiral stimulus, up to a specific angular velocity value beyond which the response saturated. However, the median response of the neurons was also a function of the number of arms in the rotating spiral (which correlates with spatial frequency) (Ibbotson et al, 2017). In flies, the lobula plate tangential cells integrate inputs from local motion detectors and respond to wide-field motion (for a detailed review see Borst et al, 2010).…”
Section: Discussionmentioning
confidence: 99%